You cannot solve it since only one side of an equation is given. If the equation was y4 + 5y2 - 84 = 0 then y4 + 12y2 - 7y2 - 84 = 0 or y2*(y2 + 12) - 7*(y2 + 12) = 0 or (y2 - 7)*(y2 + 12) = 0 then y2 = 7 or y2 = - 12 y = +or- sqrt(7) and, if you are in the complex domain, also y = +or- i*sqrt(12) where i is the imaginary square root of -1.
Chat with our AI personalities
1/5y2+9
-5y2+3x+2y
That is the most simplifiable version of this equation.
Multiply each item by 10 to give whole numbers then move items to give ay2+by+c=0 3.5y2+2.6y-8.2=4y2-6.9y multiply by 10 35y2 + 26y - 82 = 40y2 -69y subtract 35y2 from both sides 26y - 82=5y2 -69y subtract 26y from both sides -82 = 5y2 - 95y add 82 to each side 0 = 5y2 - 95y +82 or 5y2 - 95y +82 = 0
(3x - y)(3x - 5y) and (2x + 1)(2x + 11)